Physico-Chemical Characteristics of Banana (Musa Aaa ‘William’ Cavendish) Ripened at Different Temperatures - Isa, Norhelaliah (2006)
Mature green Musa AAA ‘William’ Cavendish was obtained from a fruit trading company in Selayang, Selangor. The fruit was transported to the Postharvest Laboratory at Faculty of Agriculture, UPM for quality characteristics and chlorophyll analysis. Fatty acid analysis was carried out at the Chemistry Laboratory, Faculty of Science, UPM. The fruit was ripened at two ripening temperatures (18 and 27 oC) for 5 days. The quality characteristics analyzed included colour values (L*, a*, b*, C* and ho), firmness, soluble solids concentration (SSC), titratable acidity (TA), sugar/acid ratios, pH and vitamin C. The analyses were done at each ripening temperature (18 and 27 oC) and each ripening day (Day 0, 1, 2, 3, 4 and 5). During ripening at 18 oC, L*, a*, b* and C* of Cavendish peel increased rapidly (P<0.01) while ho decreased rapidly (P<0.01) indicating that the mature-green peel had changed to full yellow. The change of peel colour was due to the reduction (P<0.01) in chl a, chl b and total chl of the peel throughout ripening days. The full yellow peel was associated with a soft and sweet pulp as evidenced by the decrease of firmness and an increase of SSC and sugar/acid ratios. TA and vitamin C reached a maximum value at ripening day 3.14 and 2.85, respectively, while pH reached a minimum value at ripening day 2.71. Myristic, palmitic, stearic, oleic, linoleic and linolenic acid were found in Cavendish banana peel. The additional of two other fatty acids were found in Cavendish banana pulp; palmitoleic and hexadecadienoic acid. However, only palmitic, linoleic and linolenic acid showed significant changes when ripened at 18 oC and 27 oC. During ripening at 18 oC, palmitic, linoleic and linolenic acid increased linearly both in the peel and pulp. When ripened at 27 oC, palmitic, linoleic and linolenic acid in the peel and pulp showed a quadratic decrease. These indicated that the change of fatty acids in the peel was associated with the change of fatty acids in the pulp either ripened at 18 o C or 27 oC. During ripening at 27 oC, L*, a*, b* and C* of Cavendish banana peel increased slowly (P<0.05) while ho decreased slowly (P<0.05), thus resulting in a pale-green peel. The pale-green peel occurred due to the slow degradation (P<0.05) of chl a, chl b and total chl during ripening. Pale green Cavendish banana was associated with very soft texture and sweet tasting pulp as evidenced by a rapid loss (P<0.01) of firmness and rapid increase (P<0.01) of SSC and sugar/acid ratios. TA and vitamin C reached a maximum value at ripening day 2.93 and 2.06 respectively, while pH reached a minimum value at ripening day 2.92. Palmitic, linoleic and linolenic acid in Cavendish banana peel and pulp were significantly increased at ripening day 1 followed by a decrease until day 5 of ripening. This indicated that insufficient fatty acids in both peel and pulp during ripening had an effect in producing a pale green Cavendish banana. Results from this research can be used for gene manipulation of Cavendish banana to produce a cultivar that can be ripen normally at tropical temperature by inducing palmitic, linoleic and linolenic acid during genetic modification process.